Construction of a Class of Copula Using the Finite Difference Method. (24th July 2021) - Bagré, Remi Guillaume; Béré, Frédéric; Loyara, Vini Yves Bernadin
Abstract : The definition of a copula function and the study of its properties are at the same time not obvious tasks, as there is no general method for constructing them. In this paper, we present a method that allows us to obtain a class of copula as a solution to a boundary value problem. For this, we use the finite difference method which is a common technique for finding approximate solutions of partial differential equations which consists in solving a system of relations (numerical scheme) linking the values of the unknown functions at certain points sufficiently close to each other.